Passive Immunization of Anti bZP3 (Zone Pellucida3) in Wistar Rat (Rattus novergicus) and Mouse (Mus musculus) - Y Pantiwati (Media Peternakan, 2012)
This study was aimed at comparing the influence of anti bZP3's passive immunization on anti-anti bZP3's titer and pregnancy level on Wistar rats and mice. This study employed factorial design experiment with completely randomized design. The first factor was immunogenic type. The treated rats were immunized with 100 L anti bZP3 in 100 L Complete Freund's Adjuvant (CFA), while the treated mice were injected with 50 L anti bZP3 in 50 L CFA. Control Wistar rats and mice were immunized with CFA and Incomplete Freund's Adjuvant (IFA) without anti bZP3. The second factor was animal type. The third factor was the length of serum incubation, i.e. 38, 49, 63, 86, 100, and 126 d. Dot blot on the treated Wistar rats and mice showed positive response proven by blue gradation; pre-immune mice as well as control Wistar rats and mice showed negative response proven by white gradation. The highest antibody titer in treated mouse serum was shown in 63 d incubation. The pregnancy on treated mice, control mice and Wistar rat occurred 100% until day 126; while the failure percentage on the treated mice was 4.5%. The pregnancy on treated mice occurred in 86 d incubation (1 rat), 100 d incubation (1 rat), and 126 d incubation (3 rats). Effective passive immunization on similar hospes occurred until day 63; while different hospes was ineffective. Antibodi anti-bZP3 was potential as a contraception through passive immunization on similar hospes.